(3CWQGa GdCaQGO ddOGQbWfis - (3GHf GdbjSQGfj , eMeO Hf WGgQ Hf eMeO GdebOSj, CHh GdaVd,J (B507 (3g` s ((3GdEScfOQjI s)
(3ChdgG (B:s
(3GdMeO ddg CeG HYO aEf CHG GdMSf GdOGQ bWfi GdMGaX QMeg Gddg NQL dfaSg ahGFO ef GdZQGFH hGdEaQGO s
(3BNQgG (B:s
(3MOjK Ce OGhO Hf UGdM (B: (3Cf ehdGJgG CQSdJgG Edi YGFTI hajg GdgQI djSJ HfLS JaQO Hg YHO GdYRjR Hf UGdM Yf Ceg HgPg GdCdaGX BNQ GdCWQGa hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3YdjgG JMHjS CHj GdYHGS GdefUhQ HGddg Ydi LGeY GdbRhjjf HaGS HJGQjN YGe (B1009 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B171 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B98s
Keywords: (3GdMOjK h GdeUWdMs